THE EVOLUTION OF INDIA’S ‘COUNTER-TERRORISM (CT)’ POLICY IN THE 21ST CENTURY - Ashok, Mule Rohit (UI Scholars Hub, 2025)
The changing nature of modern terrorism has proved a major threat to the global security architecture. The 9/11 terrorist attack on the United States of America, the world's ‘Police State’, is apparent. Consequently, the international community launched collective fights at different levels to deal with it. However, the nation-state at the individual level also designed a ‘Counter-Terror (CT)’ policy mechanism within the scope of the foreign policy paradigm to safeguard national security. India, since its independence, has consistently faced security challenges from terrorism from its neighbours, and has followed the same suit. The major CT policy was grounded in the post-2001 period, when an attack on the Parliament happened. ‘Zero Tolerance with Terrorism’ is the principal ideology on which India’s entire CT policy framework is built. Of course, it led to the ‘securitisation’ of foreign policy by prioritising national security above all other interests. This research paper has a major objective to analyse the evolution of CT narratives within India’s foreign policy, for which primary and secondary literature have been utilised. Recommendations of the research include that to wipe out ambiguity, the Indian government must publish a white paper concerning a coherent ‘National Terrorism Policy’.